Organisation of the beef cattle sector in the autonomous community of the Basque country (Spain) - Ruiz R.; Mandaluniz N.; Amenabar M.E.; Beltrán de Heredia I.; Oregui L.M.; Arranz J.; Ugarte E. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The beef cattle sector has experienced significant changes in the Autonomous Community of the Basque Country (BC) since Spain joined the EU in 1986. Although its level of organisation is still lower in comparison to more traditional activities (dairy sheep and cattle), an important number of structures have been set up to work in favour of its development. On the base, there are Local Breeders Associations at the province level (Alava, Bizkaia and Gipuzkoa) for each of the main breeds raised, and the corresponding Management Centres (cooperatives that provide services to farmers and farmers associations), all of them keeping close links to the local administrations (Diputaciones Forales or County Councils). At the BC level, promoted from the Basque Government, there are agents providing services in R+D (Neiker); high-quality computer services (IKT); training and education (Itsasmendikoi); development and marketing of high-quality products (Kalitatea Foundation); genetics (Aberekin); food safety (Elika) and marketing (Gurokela).
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)